Silane Mediated Amidation and Difluoroethylation Reactions Using Carboxylic Acids - Pugh, Oska (2024)
Initial discussion centres firstly around silicon and its use within synthetic organic chemistry with a particular focus on organosilicon reagents as reductants. Secondly there is a brief discussion on the importance of metal free chemistry.